Increasing Children's Interest in Learning the Qur'an Using the Muyassar Method in Conjunction with the English Language - Rochmat, Cecep Sobar; Huwaida, Jaziela; Az Zahra, Farah; Lifdhita, Salsabilla; Maulaya, Rosendah Dwi (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
The interest in learning the Qur'an has started to rise amidst the current era of moral degradation among children and adolescents. Effective Qur'an learning must be adapted to existing conditions. To address the dual global challenges of increasing interest in Qur'an learning and English language education, an integrated method is required. This paper aims to provide an understanding of the importance of Qur'an and English language education using the Al-Muyassar Qur'an learning method. This research employs a literature review method. The results of the study indicate that teaching the Qur'an to young children using the Muyassar method is highly accurate and effective, allowing children to fluently and rhythmically recite the Qur'an from an early age. With the Muyassar method, a teacher is required to extend the time for Qur'an revision (muraja'ah) to strengthen the child's memory retention. While this integrated learning method offers various advantages, it also comes with certain drawbacks. Therefore, further research on this integrated method is necessary.